The Transportation Revolution and its Consequences: The Railway Freight Rate Controversy of the Late Nineteenth Century - Cruikshank, Ken (Historical Papers / Communications historiques, 1987)
AbstractBy the turn of the century, a growing coalition of business and political leaders came to share a common goal — the creation of a national regulatory commission to control railway freight rates. The development of a coordinated railway network and advances in locomotive technology made possible a general decline in transportation costs. Business leaders consequently became concerned with the uneven way in which the private rate-making process distributed the benefits of the transportation revolution, particularly declining freight rates. In eastern Canada, they blamed railway rate-making policies for disrupting established patterns of trade. In western Canada, they castigated railway officials for failing to adjust the rate structure in response to the rapid development of new centres of economic activity. At the same time as it made possible the development of large-scale mercantile and industrial enterprise, then, the transportation revolution also created demands for a significant expansion of the state's authority over the largest of all nineteenth-century industries, the railway.